Fine-structure relaxation of O(3P) induced by collisions with He, H and H2. Issue 2 (13th November 2017) - Lique, F; Kłos, J; Alexander, M H; Le Picard, S D; Dagdigian, P J
Abstract: The excitation of fine-structure levels of O( 3 P ) by collisions is an important cooling process in the interstellar medium (ISM). We investigate here spin–orbit (de-)excitation of O( 3 P j,   j  = 0, 1, 2) induced by collisions with He, H and H2 based on quantum scattering calculations of the relevant rate coefficients in the 10–1000 K temperature range. The underlying potential energy surfaces are derived from highly correlated ab initio calculations. Significant differences were found with the rate coefficients currently used in astrophysical applications. In particular, our new rate coefficients for collisions with H are up to a factor of 5 lower. Radiative transfer computations allow the assessment of the astrophysical impact of these new rate coefficients. In the case of molecular clouds, the new data are found to increase slightly the flux of the 3 P 1 → 3 P 2, while decreasing the flux of the 3 P 0 → 3 P 1 line. In the case of atomic clouds, the flux of both lines is predicted to decrease. The new rate coefficients are expected to impact significantly the modelling of cooling in astrophysical environments while also allowing new insights into oxygen chemistry in the ISM.